Development of a validated HPLC method for determination of an active component in Pycnocycla spinosa and tablets prepared from its extract - Naser Tavakolli; Mustafa Ghanadian; Gholamreza Asghari; Hassan Sadraei; Nadia Asgari Borjlou; Majid Tabakhian (Shahrekord University of Medical Sciences, 2017)
Introduction: Pycnocycla spinosa, a native plant of Iran with approved antispasmodic and antidiarrheal activities, could be a suitable candidate and an alternative remedy for the treatment of diarrhea and irritable bowel syndrome (IBS). Therefore, the aim of this study is formulation of an acceptable dosage form and development of a validated high-performance liquid chromatography (HPLC) method for analysis of active ingredients in its extract and pharmaceutical forms. Methods: Different formulations of P. spinosa tablets were prepared by wet granulation method. The prepared tablets were evaluated for hardness, friability, disintegration time and drug assay. HPLC was carried out based on the extract active ingredient: 6-(4-hydroxy-3-methoxyphenyl)-hexanoic acid (HMPHA) determination in P. spinosa extract and tablets. Results: The mean weight, friability, hardness, and disintegration time of selected formulation (tablet 5 mg) were 217.26 mg, 0.69%, 53.6 N and 95.8 seconds, respectively. Similar acceptable results were also found for 10 mg tablets. The assay test showed that the content of HMPHA in each 5 mg and 10 mg tablets were 1.64 μg and 3.59 μg, respectively. The HPLC method showed a good linearity and suitability in its working range: 4.5 to 15 μg/mL. Conclusion: The data showed that the selected formulation of P. spinosa tablets has acceptable physicochemical features.